Access to credit for real estate transactions in emerging markets - Empirical evidence from Vietnam - Khuc, The Anh; Nguyen, Manh Cuong; Nguyen, Ha Anh; Vu, Hoang Anh; Nguyen, Quoc Tien (Journal of International Economics and Management, 2024)
The growing disparity between the wealthy and the poor has become more evident than ever, as reflected in residents’ housing conditions. Meanwhile, real estate credit is mainly directed towards the high-end segment, but mortgage cash flow for social and commercial housing in the low-mid range segment is still insufficient. Consequently, there is an asymmetry between the requirements for meeting housing needs and household income. This study investigates the impact of attitudes, credit accessibility, and policies on individuals’ borrowing intentions in real estate transactions. Structural equation modeling was employed to analyze the data obtained from 889 Vietnamese respondents. The results show that policies and attitudes directly impact people’s intentions to access credit. Meanwhile, credit accessibility indirectly affects this intention. These findings can serve as the basis for financial institutions to devise secure, accessible, and efficient loan policies for individuals with legitimate needs. Specifically, lending institutions should improve the quality of their services and increase their assistance to borrowers. The government should enact a stronger legal framework to address public housing demand and efficiently regulate the real estate market.